VALUASI EKONOMI EKOSISTEM MANGROVE DI DESA TANJUNG LIMAU KECAMATAN MUARA BADAK KABUPATEN KUTAI KARTANEGARA PROVINSI KALIMANTAN TIMUR - Firman, Agus; Oktawati, Nurul Ovia; Ningsih, Etik Sulistiowati (EnviroScienteae, 2024)
The objective of this research to identify the benefits economic value of mangrove ecosystem, Counting the benefits directly or indirectly, and the benefits of the existence and choice of mangrove resources efficiently and sustainably. This research was conducted in November to Desember 2023 at Desa Tanjung Limau Kecamatan Muara Badak Kabupaten Kutai Provinsi Kalimantan Timur. The research method used Qualitative Descriptive, with a total of research samples is 89 were selected using purposive sampling. The results of this research shows that the direct utilization of the mangrove ecosystem by the public, both as a subsistence and commercial business, is a utilization of the results of ponds, fishing and cage cultivation of pigeon cockle. The type of utilization with the highest optimal direct benefit value a year is catching Rp. 6,887,400,000.00 so that the optimal profit is Rp. 5,629,540,617.00 a year for 11 (eleven) RTP. The lowest optimal profit is Rp. 390,000,000.00 from utilization of pigeon cockle cultivation and the highest benefit value of mangrove forests is indirect benefits, there has a largest percentage compared to other benefits, total percentage is 87.294% as big as Rp.63,948,330,747.00 annually.